Benchmarking Practices in the Information and Documentation Centers - Kurulgan, Mesut (Information World, 2007)
Prior to 1980’s most of the Information and Documentation Centers (IDC) had adopted customer satisfaction as the quality criterion of their services. During the 80’s IDC’s became aware of Total Quality Management as one of the primary influencing factors in increasing the efficiency of information services and began its implementation. For over 20 years they have been using instruments and processes to improve services offered to users. One of these is benchmarking. Different benchmarking processes such as those of competitive, cooperative, internal, quantitative and qualitative types were all utilized by IDC’s. This study briefly explains the benchmarking process and examines various practices of benchmarking in Information and Documentation Centers in the World and in Turkey.